Bloody flukes: a review of aporocotylids as parasites of cultured marine fishes. Issue 10 (September 2020) - Power, Cecilia; Nowak, Barbara F.; Cribb, Thomas H.; Bott, Nathan J.
Graphical abstract: Highlights: Severe infections of blood flukes have been associated with mass mortality events in cultured marine species of teleosts. Molecular techniques have played an important role in understanding the biology and ecology of fish blood flukes. Praziquantel is the only known treatment option and its continued efficacy will need to be monitored. Abstract: Fish blood flukes (Digenea: Aporocotylidae) are important pathogens of fishes in aquaculture. Severe infections have been associated with mass mortality events in cultured marine species of teleosts in Australia, Asia and Europe, leading to significant socio-economic losses. Here we review recent advances towards understanding the biology and ecology of fish blood flukes, and the integral role molecular techniques have played in this development. Techniques include molecular matching of aporocotylid life stages using ITS-2 rDNA, and targeting ITS-2 rDNA to distinguish aporocotylid species using quantitative PCR (qPCR). These approaches have facilitated the elucidation of multiple life cycles for species of Cardicola infecting bluefin tunas Thunnus spp. cultured in Australia and Japan. Continued work to identify intermediate hosts of fish blood flukes is critical to improve understanding of their life cycles and help inform aquatic animal health management e.g. through site selection and/or separation of intermediate and definitive hosts. As praziquantel is the only known treatment option for infected fish, its continued efficacy will need to be monitored and other possible solutions may need to be identified as aquaculture continues to grow and diversify.